Legal Protection for Experts in Providing Visum et Repertum to Accused People with Mental Disorders - Suyatno*, Suyatno; Dwi Kurniawan, Itok (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2023)
Experts are parties who play a very important role in obtaining material truth in a criminal case. Law enforcement officers certainly need to get help from experts in fields of knowledge they don't understand. One of them is in determining the mental condition of a defendant who is suspected of committing a criminal act in relation to his ability to take responsibility for his actions. The problem that often arises is when the psychiatrist's information may contain inaccuracies, which raises concerns that the expert could be blamed under criminal law for the information he provides. This article was written using a normative legal research method with a statutory approach. The results of this research are that psychiatric experts (psychiatrists) have received protection in Law Number 13 of 2006 concerning Protection of Witnesses and Victims, so that in providing information, experts cannot be blamed because the expert has been bound by an oath of office and has expertise based on his science.